A coaches roundtable (coaching the 400-meter hurdles) - Thorson, M. (Techniques Magazine, 2023)
Summary: Change ist constant and the great coaches embrace it and understand that there ist always more to learn. It is difficult to learn, however, when you know everything, and I have encountered more and more coaches in recent years that fall into that catergory. Most of us will agree that great coaches have a passion and are in constant pursuit of excellence. They are always challenging themselves to get better. A principle from the legendary basketball coach John Wooden of UCLA, certainly applied to this: "It´s what you learn after you know it all that counts." It is out hope that this articel can inspire and encourage coaches to continue to learn and provide them with an awareness and understanding that will guide them in their ques for success and excellence in their 400 meter hurdles training programs for their athletes.